2020
DOI: 10.33137/cpoj.v3i1.33931
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Physical Activity Outcomes in Rehabilitation Interventions for Lower Limb Amputees: A Systematic Review

Abstract: BACKGROUND: Interventions which have focused on improving the physical activity of individuals with lower limb amputation can be mostly categorized into behavioural-based and prosthetic-based interventions. The aim of this review was to assess the quality of these interventions, and to identify the key gaps in research in this field. METHODOLOGY: The databases of Scopus, Pubmed, Embase, Medline and Web of Science were searched between September and December of 2019 for articles relating to physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Objective physical activity monitoring of lower limb amputees can be achieved using wearable sensors, however the literature has shown that simplistic objective monitoring (for instance, measuring step count or energy expenditure) is overwhelmingly favoured (Jamieson et al, 2020). For a more detailed analysis of activity, the implementation of machine learning algorithms to recognize wider varieties of activity is a logical solution.…”
Section: Introductionmentioning
confidence: 99%
“…Objective physical activity monitoring of lower limb amputees can be achieved using wearable sensors, however the literature has shown that simplistic objective monitoring (for instance, measuring step count or energy expenditure) is overwhelmingly favoured (Jamieson et al, 2020). For a more detailed analysis of activity, the implementation of machine learning algorithms to recognize wider varieties of activity is a logical solution.…”
Section: Introductionmentioning
confidence: 99%